2014
DOI: 10.1589/jpts.26.139
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Thai Exercise with Traditional Massage on the Pain, Walking Ability and QOL of Older People with Knee Osteoarthritis: A Randomized Controlled Trial in the Community

Abstract: [Purpose] This study investigated the effectiveness of a class- and home-based exercise with massage between Thai traditional and standardized physical therapy (TPT and SPT) in older people with knee osteoarthritis (KOA). [Subjects and Methods] Thirty-one subjects with KOA (aged 50–85 years) in two selected villages were randomly assigned into the TPT or SPT programs. Seventeen TPT subjects received Thai exercise with traditional massage, and 14 SPT individuals performed strengthening exercise with Swedish mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“… 3 , 5 Proper assessment of muscle function on physical activities prior to exercise training is important for individuals to provide a better exercise prescription at home or at the community center. 34 , 35 …”
Section: Discussionmentioning
confidence: 99%
“… 3 , 5 Proper assessment of muscle function on physical activities prior to exercise training is important for individuals to provide a better exercise prescription at home or at the community center. 34 , 35 …”
Section: Discussionmentioning
confidence: 99%
“…20 Punee et al in an RCT investigated the effectiveness of a class and home-based exercise with massage between Thai traditional (TPT) and standardized physical therapy (SPT) in older people with knee OA. 21 They found significant improvement in both groups, but the improvement of the TPT group was greater.…”
Section: Physical Therapymentioning
confidence: 93%
“…A study comparing Thai massage with Swedish massage in a sample of older people with knee osteoarthritis supports the need for moderate pressure [2]. In this study the group that received Thai massage (which generally involves more pressure) reported a greater reduction in pain on the WOMAC than the group that received Swedish massage.…”
mentioning
confidence: 57%
“…However, on more objective measures such as range of motion (ROM), these four studies are inconclusive. This would relate to ROM not being measured in two of the studies [1,2]. In the first of these, pain was measured using a 10-point Likert scale, and pain decreased even though only the patient's healthy foot, hands and upper parts of the shoulders were massaged "shallowly" for 20 min each day of their hospitalization [1].…”
mentioning
confidence: 99%